Intramyocardial immunomodulation with human CD16+ monocytes to treat myocardial infarction in pig: a blind randomized preclinical trial - Ascione, Raimondo; Bruno, Vito D.; Johnson, Tom; Sammut, Eva; Bond, Andrew; Lopez-Baz, Daniel; Deutsch, Julia; Bailey, Mick; Chiribiri, Amedeo; Patel, Ashish; Baker, Andrew; Modarai, Bijan (Frontiers in Cardiovascular Medicine, 2024)
Human CD16 + monocytes (hCD16 + Ms) have pro-angiogenic properties. We assessed the feasibility, safety and efficacy of hCD16 + Ms in a porcine model of myocardial infarction (MI).27 female Large-White pigs underwent MI with reperfusion and cardiac magnetic resonance (CMR).Five days later animals received intramyocardial injections of hCD16 + Ms in saline (n=13) or saline only (n=14). hCD16 + Ms were selected from leucocyte cones. Feasibility/safety endpoints included injury at injected sites, malignant arrhythmias, cancer, haematoma, left ventricular (LV) dilatation, troponin release and downstream organ injury. Co-primary efficacy outcome included LV scar and ejection fraction (LVEF) at 30-day post-injections by CMR. Immunohistochemistry included neo-angiogenesis, fibrosis, markers of myofibroblast and inflammation. Four animals were excluded before injections due to untreatable malignant arrhythmias or lung injury. Median cell number and viability were 48.75 million and 87% respectively. No feasibility/safety concerns were associated with the use of hCD16 + Ms. The LV scar dropped by 14.5gr (from 25.45±8.24 to 10.8±3.4 gr; -55%) and by 6.4gr (from 18.83±5.06 to 12.4±3.9gr; -30%) in the hCD16 + Ms and control groups respectively (p=0.015). 30-day LVEF did not differ between groups, but a pre-specified sub-analysis within the hCD16 + Ms group showed that LVEF was 2.8% higher and LV scar 2.9gr lower in the subgroup receiving higher celldose. Higher tissue levels of neo-angiogenesis, myofibroblast and IL-6, and lower levels of TGF-β were observed in the hCD16 + Ms group.The use of hCD16 + Ms in acute MI is feasible, safe and is associated with reduced LV scar size, increased tissue levels of neo-angiogenesis, myofibroblasts, IL-6 and reduced pro-fibrotic TGF-β at 30-day postinjections. A higher cell-dose might increase LVEF effect while reducing scar size, but this warrants validation in future studies.